2021
DOI: 10.3390/md19070402
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structural Characterization and Antidiabetic Activity of New Diketopiperazine Alkaloids from Mangrove Endophytic Fungus Aspergillus sp. 16-5c

Abstract: Six new DIKETOPIPERAZINE alkaloids aspergiamides A–F (1–6), together with ten known alkaloids (7–16), were isolated from the mangrove endophytic fungus Aspergillus sp. 16-5c. The structures of the new compounds were elucidated based on 1D/2D NMR spectroscopic and HR-ESIMS data analyses. The absolute configurations of aspergiamides A-F were established based on the experimental and calculated ECD data. All the compounds were evaluated for the antidiabetic activity against α-glucosidase and PTP1B enzyme. The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…The theoretical approach is important, especially for DKPs that are not readily obtained by synthesis. In fact, theoretical ECD has recently become an important approach for stereochemical analysis of structurally complex DKPs from natural sources [ 21 , 22 ]. Another possible alternative approach is the use of vibrational CD (VCD), which has become a powerful method for determining absolute configuration of natural products [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical approach is important, especially for DKPs that are not readily obtained by synthesis. In fact, theoretical ECD has recently become an important approach for stereochemical analysis of structurally complex DKPs from natural sources [ 21 , 22 ]. Another possible alternative approach is the use of vibrational CD (VCD), which has become a powerful method for determining absolute configuration of natural products [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antihyperglycaemic activity of DKPs is well-documented in the literature [310,311]. Proline-based DKP alkaloids, from marine fungi, can provide a new platform for the discovery of a drug [312]. Cyclo(His-Pro) decreases the level of blood glucose [176].…”
Section: Cardio-metabolic Disordersmentioning
confidence: 99%
“…DKP alkaloids are important secondary metabolites of microbes. Indole DKP alkaloids are the condensation products of tryptophan with a second amino acid-like L-proline [105,312,331].…”
Section: Activators Of Dioxygen In Oxidative Processesmentioning
confidence: 99%
“…The genus Aspergillus is omnipresent among almost all ecosystems even the circumpolar maritime regions [ 1 ]. Previous investigations on Aspergillus genus indicated that it was rich in bioactive secondary metabolites with multifarious and intricate structures such as sesquiterpenoids [ 2 , 3 ], meroterpenoids [ 4 , 5 ], alkaloids [ 6 , 7 ], and polyketides [ 8 ]. Some of the natural products isolated from Aspergillus genus possessed cytotoxic, antimicrobial, acetylcholinesterase inhibitory, and PTP1B enzyme inhibitory activities [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], which have attracted great interest of natural chemists.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations on Aspergillus genus indicated that it was rich in bioactive secondary metabolites with multifarious and intricate structures such as sesquiterpenoids [ 2 , 3 ], meroterpenoids [ 4 , 5 ], alkaloids [ 6 , 7 ], and polyketides [ 8 ]. Some of the natural products isolated from Aspergillus genus possessed cytotoxic, antimicrobial, acetylcholinesterase inhibitory, and PTP1B enzyme inhibitory activities [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], which have attracted great interest of natural chemists. Bisabolanes, a class of sesquiterpenoids possessing diverse skeletons including aromatic monomers and their home/hetero-dimers, are mainly distributed in plant kingdom, marine-derived animals, and fungi [ 9 ].…”
Section: Introductionmentioning
confidence: 99%